2019
DOI: 10.1002/dmrr.3245
|View full text |Cite
|
Sign up to set email alerts
|

Influence of fetal sex on perinatal outcomes in women with gestational diabetes mellitus

Abstract: Background Fetal sex has recently been considered to be related to maternal glucose homeostasis and perinatal outcomes during pregnancy. Here, we investigated the effects of fetal sex on the perinatal outcomes of pregnancies with normal glucose tolerance (NGT) and gestational diabetes mellitus (GDM). Methods This was a retrospective cohort study of 1292 women with NGT and 1155 women with GDM. Pregnant women were divided into four groups according to the maternal glucose level and fetal sex. Logistic regression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…A recent study in a population with GDM found higher birthweight, fat mass and a larger placenta at birth among male vs female neonates, and a more frequent need for insulin treatment in their mothers [16]. Hu et al, [40] found a higher risk for neonatal infection, acute respiratory disorders and abnormal neonatal central nervous system development in male vs female fetuses in pregnancies with GDM. Lastly, a higher BMI and risk for obesity during childhood was observed among male but not female offspring from GDM exposed pregnancies [41].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…A recent study in a population with GDM found higher birthweight, fat mass and a larger placenta at birth among male vs female neonates, and a more frequent need for insulin treatment in their mothers [16]. Hu et al, [40] found a higher risk for neonatal infection, acute respiratory disorders and abnormal neonatal central nervous system development in male vs female fetuses in pregnancies with GDM. Lastly, a higher BMI and risk for obesity during childhood was observed among male but not female offspring from GDM exposed pregnancies [41].…”
Section: Discussionmentioning
confidence: 97%
“…In the general population, fetal growth is also monitored without consideration for fetal sex, even though some sexspeci c growth charts exist [36,37]. Regarding neonatal complications, previous population-based studies, have shown that male sex was an independent risk factor for adverse perinatal outcomes, including preterm birth, lower Apgar scores, macrosomia, [15,[38][39][40] as well as higher birthweight, and lower arterial pH [36,40]. A higher risk for pregnancy complications has been also found for women carrying male fetuses, with higher incidence of gestational diabetes, failure to progress during the rst and second stages of labor, caesarean section, cord prolapse and nuchal cords [15].…”
Section: Discussionmentioning
confidence: 99%
“…In the general population, fetal growth is also monitored without consideration for fetal sex, even though some sex-specific growth charts exist [ 42 , 43 ]. Regarding neonatal complications, previous population-based studies, have shown that male sex was an independent risk factor for adverse perinatal outcomes, including preterm birth, lower Apgar scores, macrosomia, [ 23 , 44 46 ] as well as higher birthweight, and lower arterial pH [ 42 , 46 ]. A higher risk for pregnancy complications has been also found for women carrying male fetuses, with higher incidence of gestational diabetes, caesarean section, cord prolapse and nuchal cords [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study in a population with GDM found higher birthweight, and fat mass at birth among male vs female neonates, and a more frequent need for insulin treatment in their mothers [ 24 ]. Hu et al, [ 46 ] found a higher risk for neonatal infection, acute respiratory disorders and abnormal neonatal central nervous system development in male vs female fetuses in pregnancies with GDM. Lastly, a higher BMI and risk for obesity during childhood was observed among male but not female offspring from GDM exposed pregnancies [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sex differences in various respiratory outcomes have been described previously in the pediatric population. A robust body of evidence has shown that both premature and term male infants are at higher risk of respiratory distress syndrome and respiratory infections, and are more likely to require mechanical ventilation and supplemental oxygen after birth [ 32 , 33 , 34 , 35 , 36 ]. Interestingly, in a population of formerly premature children evaluated at one year of age, males were more likely to have higher functional residual capacity, airway resistance, hyperinflation, and evidence of air trapping than their female counterparts [ 36 ].…”
Section: Discussionmentioning
confidence: 99%